1954
DOI: 10.1084/jem.100.4.363
|View full text |Cite
|
Sign up to set email alerts
|

The Purification of Hypertensin I

Abstract: The purification of hypertensin I has been described. The final product which is four times as powerful a pressor agent as l-arterenol, is obtained with an over-all recovery of 40 per cent. The product consists of a single component in countercurrent distribution, having a nitrogen content of 15.97 per cent and a specific activity of 7050 Goldblatt units per mg. of N or 1125 units per mg. of solid. Acid hydrolysis and paper chromatography indicate in a preliminary fashion that there are about nine amino acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

1961
1961
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(33 citation statements)
references
References 9 publications
2
29
0
2
Order By: Relevance
“…In 1958, the pressor substance was named angiotensin* 1954 Discovery of Ang I and Ang II, and ACE --Skeggs et al [18].…”
Section: 1940mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1958, the pressor substance was named angiotensin* 1954 Discovery of Ang I and Ang II, and ACE --Skeggs et al [18].…”
Section: 1940mentioning
confidence: 99%
“…The discovery of renin, as a hypertensive factor in extracts of rabbit kidney, was appreciated many years later when it was shown that it had an important role in the experimental models of hypertension ( Table 1). In 1956, Skeggs and coworkers [18] discovered ACE, an enzyme which converts Ang I to Ang II, and they published the amino acid sequence of Ang II. On the basis of collected information, the classic concept on the RAS came out: renin is released from renal juxtaglomerular cells into the blood where it converts angiotensinogen to Ang I.…”
Section: Formation Metabolism and Actions Of Angiotensinsmentioning
confidence: 99%
“…It is the only known substrate for renin, and is cleaved at a position between 10 and 11 amino acids to generate angiotensin I (Ang I). Skeggs's group was the first to successfully purify Ang I and Ang II from horse plasma with large quantities of hog renin [3][4][5]. Subsequent studies by this same group characterized ACE, the enzyme which converts Ang I to Ang II [6].…”
Section: Introductionmentioning
confidence: 99%
“…Landis et al, 3 "' using kidney extracts presumably containing reuin, noted no change in the skin temperature of the rabbit ear. Corcoran and Page, 20 using angiotonin, found no change in the skin temperature of the dog.…”
Section: Skin Flow and Resistancementioning
confidence: 99%